Pengaruh Kompleksitas Tugas, Skeptisme dan Self-efficacy Terhadap Audit Judgement - Andhika Dhevara; Sophia Andini (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study discusses the evaluation of task commitment, skepticism and self-efficacy of audit judgement. This research was conducted at a Public Accounting Firm using probability sampling method with simple random sampling technique using primary data. Questionnaire data analysis was carried out by multiple regression using SPSS version 25 application. The population of this study were auditors working in the Jakarta Public Accountant Office and obtained sample of 80. The results showed that skepticism and self-efficacy had a positive effect on audit judgement and task effectiveness had no effect on audit judgement. As for task effectiveness, skepticism and self-efficacy together influence audit judgment.